Digital Authentic Media Exposure and Listening Development in Arabic as a Foreign Language: A Corpus-Informed Approach - Rosyad, Muh. Sabilar; Nuruddin, Ahmad; Makinuddin, Mohammad; Rozaq, Muhammad Abdur; Hafidz, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
The integration of authentic materials in language education has increasingly emphasized the importance of exposing learners to natural language input that reflects real-world communication. However, the pedagogical use of digital authentic media in Arabic as a foreign language (AFL) listening instruction remains limited, and corpus-informed approaches to analyzing such materials are still underexplored. This study investigates the impact of digital authentic media exposure on AFL learners’ listening development while examining the linguistic characteristics of Arabic digital media through corpus analysis. A mixed-method design was employed involving 30 intermediate-level learners at UIN Sunan Kalijaga Yogyakarta. The study combined corpus-informed analysis of Arabic news broadcasts and podcasts with a quasi-experimental classroom intervention using pre-test and post-test listening assessments. The results revealed that authentic Arabic media contain high lexical density and recurrent discourse markers, providing linguistically rich listening input. Learners exposed to digital authentic media demonstrated significantly greater improvement in listening comprehension and vocabulary recognition than those using textbook-based materials. The findings highlight the pedagogical potential of corpus-informed authentic media for enhancing listening development in Arabic language learning.